High glucose concentration in pericardial fluid: An indication for iatrogenic cardiac tamponade in a neonate - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
We present a case of neonatal pericardial tamponade due to umbilical venous catheterization, a rare, but life threatening complication. A newborn who developed sudden clinical deterioration at 44th hour following umbilical venous catheterization, is reported. Echocardiography showed marked pericardial effusion. Urgent pericardiocentesis was performed. Analysis of pericardial fluid revealed high glucose level consistent with the composition of total parenteral nutrition fluid being infused through the catheter. Pericardial tamponade should be considered in any infant with a central venous catheter who suddenly deteriorates and urgent pericardiocentesis should be attempted.
Keywords: Umbilical venous catheterization; Complication; Cardiac tamponade; Pericardial effusion